Capsaicinoids from Capsicum annuum as an Alternative FabH Inhibitor of Mycobacterium Tuberculosis: In Silico Study - Krisnamurti, Gabriella Chandrakirana; Sari, Dewi Ratih Tirto; Bare, Yohanes (Makara Journal of Science, 2021)
The number of tuberculosis (TB) cases worldwide reached 1.5 million in 2018; thus, TB is considered a deadly disease. TB is caused by Mycobacterium tuberculosis and involves lipid synthesis. Considering the importance of lipid metabolism in bacteria, FabH may be an essential protein target for repressing lipid synthesis. Capsaicinoids from Capsicum annuum demonstrate potent antibacterial activity. This study predicted the ability of capsaicinoid compounds to inhibit FabH. In silico analysis was performed by retrieving the structure of FabH from PDB and those of selected capsaicinoid derivatives from PubChem. The compounds were docked using AutoDock Vina in PyRx 0.8 software. The interactions of FabH and different capsaicinoid derivatives showed identical binding characteristics. The bonding type most frequently observed was hydrogen bonds. In conclusion, capsaicinoid derivatives could block lipid synthesis through FabH. The relevant mechanism and biological processes should be studied further.